New species and new records of Eastern Palaearctic Stenichnus Thomson (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
Two new scydmaenine species are described based on specimens collected in Taiwan: Stenichnus (s. str.) bifurcatus sp. n., and Stenichnus (s. str.) totoroides sp. n. New records are provided for Stenichnus totoro Jałoszyński (Japan: Iriomote-jima and Ishigaki-jima), S. bellulus Jałoszyński (Taiwan; Japan: Iriomote-jima, Ishigaki-jima, and for the first time recorded from Yonaguni-jima), S. taiwanicus Franz (Taiwan), S. bicolor (Denny) (Europe, Mongolia, Siberia, Russian Far East, and for the first time recorded from Japan: Iwate Prefecture), S. dividus Kurbatov (Russian Far East; for the first time recorded from Japan: Fukushima Prefecture), S. lackneri Jałoszyński (Japan: Tokunoshima, and for the first time recorded from Amami-Ôshima and Okinawa-jima), S. pollens (Sharp) (Japan: Kyushu, and for the first time recorded from Honshu), S. minipollens Jałoszyński (Japan: Hokkaido, and for the first time recorded from Kyushu and Shikoku), and S. saltuarius Kurbatov (Russian Far East; for the first time recorded from China: Heilongjiang Province). Moreover, records of six undescribed Japanese species of Stenichnus known from females are given, to facilitate future study on the still poorly known diversity of this genus in Eastern Palaearctic. Stenichnus dividus and S. saltuarius are placed in the nominotypical subgenus.